Avian type specimens and their type localities from Otto Schütt’s and Friedrich von Mechow’s Angolan collections in the Museum für Naturkunde of the Humboldt-University of Berlin - Steinheimer, Frank D.; Dean, W. R. J. (Zootaxa, 2007)
A comprehensive list of all avian type specimens in the Angolan collections of Otto Schütt and Major Friedrich Wilhelm Alexander von Mechow housed in the Museum für Naturkunde Berlin (ZMB) is given for the new avian taxa originally described by Cabanis, Reichenow, Neumann, Grote and Neuzig in the late 19th and early 20th century. Each entry discusses the collection history of the specimens, the type locality, nomenclature and taxonomy.